2019
DOI: 10.1002/adfm.201904018
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering for Both Cathode and Anode Enables Low‐Cost Highly Efficient Solution‐Processed CdTe Nanocrystal Solar Cells

Abstract: Low‐cost solution‐processed CdTe nanocrystal (NC) solar cells always suffer from a high interface energy barrier and unbalanced hole/electron transport as well as anisotropic atom diffusion on the CdTe surface due to the limited amount of hole/electron interface materials or the difficulty in interface processing. In this work, a novel strategy is first adopted with gradient electron transport layer (CdS/CdSe) modification in the cathode and a new crosslinkable hole transport polymer (P‐TPA) implantation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…CdS NCs, CdSe NCs, CdTe NCs, and ZnO precursors were prepared based on previous reported methods [ 15 , 24 ]. Spiro (CAS: 207739-72-8) was purchased from Derthon Optoelectronic Materials Science Technology Co., Ltd. (Shenzhen, China) and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CdS NCs, CdSe NCs, CdTe NCs, and ZnO precursors were prepared based on previous reported methods [ 15 , 24 ]. Spiro (CAS: 207739-72-8) was purchased from Derthon Optoelectronic Materials Science Technology Co., Ltd. (Shenzhen, China) and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…There were several reports about using triphenylamine type polymers such as poly(diphenylsilane-co-4-vinyl-triphenylamine) (Si-TPA) or poly(phenylphosphine-co-4-vinyl-triphenylamine) (P-TPA) as a HTL. In these reports, high power conversion efficiency (PCE) up to 9% is obtained, which is the highest value ever reported for CdTe NC solar cells with an inverted structure [ 15 , 16 ]. Researchers found that strong binding exists between Cd and N atoms and a dipole layer can thus be formed, which effectively decreases interfacial recombination and improves carrier collection efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Measurements of the surface recombination velocity in detector-grade CdTe are scarce. Another important application of CdTe are solar cells [ 7 , 8 , 9 ], where most of the work of research of surface recombination velocity was done. The recombination velocity determined in untreated crystal was reported [ 10 ], while it decreased to after surface treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This has placed a great deal of emphasis on the fabrication process of photovoltaic cells that will result in better conversion efficiency than the ideal dye sensitizer solar cells (DSSC) (see Figure 1), which have been used over the past two decades. The emergence of quantum dots (QDs) sensitizer has found great relevance in the formation of many cells, such as inorganic cells, organic cells, solution-process colloidal solar cells and dye-sensitized solar cells [1,[3][4][5][6][7]. Their unique size distribution and spectra properties enable them to absorb the entire visible spectrum, resulting in an improved power conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%